Tay-Sachs disease: high gene frequency in a non-Jewish population. - Kelly, T E (1975)
A non-Amish "Pennsylvania Dutch" semi-isolate was found to have a high frequency of Tay-Sachs gene. This high frequency could be ascribed to founder effect and may represent, in microcosm, how this mechanism could have produced the high gene frequency among Ashkenazi Jews.